New chiral and flexible metal−organic framework with a bifunctional spiro linker and Zn4O-nodes - Gedrich, Kristina; Senkovska, Irena; Baburin, Igor A.; Mueller, Uwe; Trapp, Oliver; Kaskel, Stefan (Inorganic chemistry, 2010)
A new chiral Metal−Organic Framework (MOF), named DUT-7, has been synthesized from enantiopure (S)-2,2′-spirobiindane-5,5′-dicarboxylic acid ((S)-H2L) and zinc nitrate. The framework of the compound has the composition Zn4O((S)-L)3 as it is found for the IRMOF series, but in contrast to these MOFs, the crystal structure of DUT-7(RT) (RT: room temperature) which has to be assigned to the chiral space group P6322, has a completely different topology. The Zn4O clusters are not coordinated in an octahedral fashion but show only C3 symmetry and are arranged in a trigonal-prismatic manner. The framework is built of two interpenetrated nets with an acs topology related to each other by the 2-fold axes. DUT-7 is the first example of this rare framework topology constructed from Zn4O units. A reversible structural transformation was observed upon cooling during single crystal X-ray diffraction. The resulting crystal structure, denoted as DUT-7(LT) (LT: low temperature), is characterized by a Zn4O cluster not only coordinated by six linker moieties but also by two additional solvent molecules leading to an octahedral coordination of one of the zinc atoms of the cluster. This structure transformation leads to a tripled unit cell compared to DUT-7(RT) and a change of the space group to P6522. The flexibility of the coordination of the metal atoms which has been observed for the first time points toward a catalytic activity of MOFs exhibiting metal atoms with a closed shell not only caused by defects in the crystal structure. The reaction of racemic 2,2′-spirobiindane-5,5′-dicarboxylic acid (rac-H2L) with zinc nitrate lead to a microcrystalline compound DUT-7(rac). DUT-7 and DUT-7(rac) have been characterized by X-ray powder diffraction, elemental and thermogravimetric analysis, and IR spectroscopy revealing the same framework composition for both compounds. The porosity of DUT-7 and DUT-7(rac) was proven by nitrogen and hydrogen physisorption measurements.